Filter Cleaning System Modification to Improve Dust Colletor - Haolia Rahman; Alfi Hidayat Hutasuhut; Sugeng Mulyono (MBI, 2024)
The filter cleaning system is part of the dust collector which functions as a filter between dirty air and clean air. Blockage of the dust collector is due to a lack of maintenance to control the performance of filter cleaning components such as valves, jetspray tubes and bagcloth. Another cause is the less than optimal air pressure from the jetspray to dislodge the dust adhering to the bagcloth. So it is necessary to recondition both the layout of the filter cleaning components and the optimization of jet spray pressure. Determination of the capacity of the jetspray tube is adjusted to the specifications of the compressor and uses the ASME VIII Div I (Pressure Vessel) standard with dimensions of 1400mm x 8inch SCH20. The feasibility test of the jetspray tube is carried out by calculating the allowable thickness and the factor of safety based on the pressure operated on the jetspray tube. Determining the location of the filter cleaning components is based on aspects that make it easier for the operator to carry out the maintenance so that the performance of the filter cleaning components can be controlled properly. Based on the stress simulation using solidworks 2020 for the SCH20 pipe which has a thickness of 6.35mm operated with a pressure of 7 bar it is categorized as safe to use.